Chapter 8: Guilt. (Lion on the Freeway: A Thematic Introduction to Contemporary South African Literature in English, 1999)
Chapter 8 of the book "Lion on the Freeway: A Thematic Introduction to Contemporary South African Literature in English" is presented. It highlights several literary works in South Africa, which depict characters that show a feeling of guilt. These include "Waiting for the Barbarians," by J. M. Coetzee and "Master Harold … and the Boys," by Athol Fugard.